P3.278 Azithromycin Susceptibilities in Canadian Neisseria Gonorrhoeae Isolates (2010–2011). (13th July 2013) - Martin, I; Sawatzky, P; Liu, G; Lefebvre, B; Lovgren, M; Allen, V; Hoang, L; Horsman, G; Wong, T
Abstract : Background: Neisseria gonorrhoeae have developed resistance to many antibiotics and current Canadian STI guidelines recommend azithromycin as part of a combination therapy for gonorrhoea. Methods: Between 2010 and 2011, N. gonorrhoeae strains were isolated or collected by Canadian provincial public health laboratories and submitted to the National Microbiology Laboratory (NML) (N = 2392). Isolates are submitted to the NML only when the provincial laboratories identify resistance to at least one antibiotic or if the provincial laboratories do not conduct any antimicrobial susceptibility testing. Minimum inhibitory concentrations (MICs) were determined by agar dilution and the N. gonorrhoeae multi-antigen sequence typing (NG-MAST) was used for molecular typing. Possible mutations in the mtrR gene and promoter region, the 23S rRNA (4 alleles) and L22 riboprotein genes were determined by sequencing. Results: Azithromycin resistance was 3.0% in 2010 (37/1233) and 1.1% in 2011 (13/1158) amongst all the isolates tested at NML. Forty-five azithromycin resistant isolates (MICs ranging from 2 to ≥ 256 µg/ml) were characterised. The A deletion in the mtrR efflux pump were identified in 37.8% (n = 17) isolates. Additional mtrR mutations include: A39T (28.9%, n = 13) and G45D (4.4%, n = 2). One isolate was identified with mutation D89A in the L22 riboprotein. Thirty-three isolates (73.3%) were identified with the C2599T mutation in at least 1 of the 4 alleles of the 23S rRNA. The A2143G mutation was identified in all 4 alleles in the two isolates with azithromycin MICs of > = 256 µg/ml. Conclusions: With reducing susceptibility of cephalosporins as treatment for gonorrhoea, azithromycin may be relied on more to treat gonorrhoea. Rapid molecular detection of antimicrobial susceptibilities in N. gonorrhoeae is important to prevent the spread of untreatable multidrug resistant gonorrhoea.